Sleep Quality and Its Impact on Academic Performance and Memory Consolidation in Elementary School Children - Ayu Yuliani Sekriptini; Zara Ali; Rafiullah Amin (Yayasan Adra Karima Hubbi, 2025)
Sleep plays a fundamental role in the cognitive and emotional development of children, yet sleep deprivation has become increasingly common among elementary school students due to lifestyle and environmental factors. Poor sleep quality has been linked to diminished academic performance, reduced attention span, and impaired memory consolidation, all of which are essential for effective learning. This study aims to investigate the relationship between sleep quality, academic achievement, and memory consolidation processes in elementary school children. A quantitative correlational design was employed involving 280 students aged 9–12 years from three urban elementary schools. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) and a standardized memory recall test, alongside academic records. Statistical analyses were performed using Pearson correlation and multiple regression to determine predictive relationships among variables. Findings indicated a significant positive correlation between sleep quality and both academic performance (r = 0.63, p < 0.001) and memory retention (r = 0.59, p < 0.001). Children with consistent sleep schedules and adequate rest demonstrated superior cognitive function, particularly in long-term memory tasks and problem-solving abilities. The study concludes that sufficient and high-quality sleep is a critical determinant of learning efficiency and academic success. Interventions promoting healthy sleep habits should be integrated into school health programs to support cognitive and educational outcomes.